Knowledge, Attitude and Practices towards Drug Prescription for Oral Mucosal Lesions in Saudi Arabia: Life Sciences-Medicine for Novel Therapy - Dr.Horiyah Aleybani; Dr.Alanood Alzogibi; Dr.Kumar Chandan Srivastava; Deepti Shrivastava; Dr.Khalid Aljohani (International Journal of Life Science and Pharma Research, 2022)
Oral mucosal diseases are common in routine dental practices and significantly influence patients’ quality of life. Dental students should be aware about the management of oral mucosal diseases as well as the major oral diseases such as dental caries, gingivitis and periodontitis. This study aimed to evaluate, attitudes and practices of dental students regarding management of certain oral mucosal conditions. This is a cross sectional KAP study conducted among dental students in Saudi Arabia. Inclusion criteria were students in 4th academic year or higher, since these students should study the pharmacological courses starting from the 4th academic year. The sample included 300 students to whom questionnaires were distributed. Chi-square test of homogeneity was used to detect significant differences in students’ knowledge, attitudes and practices based on students’ characteristics. The level of knowledge about the studied oral mucosal diseases was high in 62.7% of dental students, while only 2% had low level of knowledge. The attitude of the students was good in 48%, however 11.7% had poor attitude towards drug prescription of the medications for theses oral mucosal diseases. The practices of the dental students in prescription of medications during their clinical training were good in 16%, while it was poor in 31% of dental students. The knowledge regarding drug prescription for oral mucosal drugs were high among the majority of dental students, however the prescription practices were poor when compare to the level of knowledge.